Selective histochemical labeling of normal rat kidney and that affected by streptozotocin-induced diabetes mellitus using lectin from Lactarius pergamenus fungus - Ambarova, N. A.; Lutsyk, A. D. (Морфологія / Morphologia / Morfologìâ, 2017)
Lectins due to the ability for specific recognition of cell and tissue glycoconjugates cover significant place in modern histochemistry. Nevertheless search for new lectins with rare and unique carbohydrate specificities remains actual. Methods. A newly purified galactose-specific lectin from Lactarius pergamenus fungus (LPFA) was applied to study micromorphology of normal rat kidney and that affected by streptozotocin-induced diabetes mellitus. Results. It was detected strong LPFA reactivity with renal corpuscles, less intensely were labeled brush border of renal tubules and plasma membranes of collecting ducts. Comparison of LPFA with closely related RCA and PNA lectins revealed certain differences in these lectins bindig both in normal kidney, as well as with organ tissues of streptozotocin affected rats. LPFA receptors sites demonstrated certain stability with respect to streptozotocin-induced metabolic violations, this observation can be used for the estimation of kidney structure alterations severity under different forms of experimental and clinical pathology. Conclusion. These results demonstrate a rather unique carbohydrate specificity of LPFA lectin, which therefore can be recommended as a reliable reagent for further histochmical and histopathological investigations.